KUE MAKSUBA WARISAN MASA LAMPAU YANG BERPOTENSI SEBAGAI DAYA TARIK WISATAWAN - Nurul Sukma Lestari; Grace Sella Winata (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
Palembang is one of the oldest cities in Indonesia. Currently Palembang is the capital of South Sumatra Province. Besides being famous for its tourist attractions, Palembang is also famous for its abundance of local food ranging from salty snacks, cakes, main courses, and many others. One of the famous local food there is the Maksuba cake. This cake, which originates from the Darussalam Kingdom era, is made from duck eggs, sugar, margarine, and a little flour. This cake is always available on religious holidays, such as Eid and Chinese New Year and is one of the offerings in traditional Palembang weddings. This cake in Palembang symbolizes love and respect. The purpose of this research is to find out the history of the Maksuba cake, what is the meaning of this cake, the method of manufacture and its current existence. The method used is qualitative with a descriptive approach. The results obtained are the Maksuba Cake originating from the era of the Palembang Darussalam Sultanate, and has a meaning as a tribute to guests and elders. The recipes and manufacturing methods used still follow traditions that have been passed down from generation to generation. And the existence of this cake is still very much sought after today. This traditional cake is recommended to be preserved so that future generations can still enjoy this cake, and this cake can be one of the objects that can attract tourists to visit Palembang.Keywords: Palembang, Maksuba Cake, Tourism Object, Tribute